2014
DOI: 10.1021/bm500839j
|View full text |Cite
|
Sign up to set email alerts
|

Red Emitting, Cucurbituril-Capped, pH-Responsive Conjugated Oligomer-Based Nanoparticles for Drug Delivery and Cellular Imaging

Abstract: Here we report the synthesis of nanoparticles based on a conjugated oligomer which is synthesized through Heckcoupling of divinylfluorene and dibromobenzothiodiazole monomers. These water dispersible nanoparticles emit in the region of red tailing to the near-infrared region of the spectrum with high fluorescent quantum yield and brightness. The nanoparticles were found to be stable in water for a prolonged time without forming any aggregates and could carry camptothecin, an anticancer drug with high loading e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 39 publications
2
72
0
Order By: Relevance
“…22,24,[47][48][49] To investigate the formation of such molecular assemblies, we examined the morphology of dye, CB7, and inclusion complex of the CB7-dye complex at different pH solutions using SEM, AFM, and optical microscopic techniques. Fig.…”
Section: Complexation Induced Morphological Changesmentioning
confidence: 99%
“…22,24,[47][48][49] To investigate the formation of such molecular assemblies, we examined the morphology of dye, CB7, and inclusion complex of the CB7-dye complex at different pH solutions using SEM, AFM, and optical microscopic techniques. Fig.…”
Section: Complexation Induced Morphological Changesmentioning
confidence: 99%
“…[44] For this purpose, poly[9, 9-bis{6(N,N-dimethylamino)hexyl}fluoreneco-2,5thienylene (PFT) was synthesized and its optical properties have been investigated in the presence and the absence of CB homologues. [45] Conjugated oligomer was synthesized through Heck coupling of divinylfluorene and dibromobenzothiodiazole monomers and has an amphiphilic nature due to the presence of tertiary alkyl amine residues as pendant of the fluorene monomer. This complex emits green and is highly fluorescent with fluorescence quantum yield of 35 %.…”
Section: Assembly Of Cucurbiturils With Conjugated Oligomers and Polymentioning
confidence: 99%
“…We have observed that this nonionic conjugated polymer can be made soluble in water through an inclusion complex formation with CB8. [45] Cationic conjugated polyelectrolytes can be used in photodynamic antibacterial chemotherapy in which cationic ammonium groups interact with the negatively charge bacterial cell membranes and the photoactive backbone of the polymers acts as a photosensitizer that can be irradiated by light to generate the reactive oxygen species for photodynamic effect. It was also observed that the morphology of the polymer PFT was affected by the presence of CB8.…”
Section: Assembly Of Cucurbiturils With Conjugated Oligomers and Polymentioning
confidence: 99%
“…Combining fluorescence imaging, encapsulation of hydrophobic guest molecules, and drug delivery, Tuncel et al reported on fluorene‐based nanoparticles which encapsulate a drug and emit fluorescence in the red region tailing to infrared (Figure ). The two fluorene units, both bearing two amine substituted side chains, are bridged by a central divinyl benzothiadiazole moiety, resulting in an oligomer bearing a hydrophobic backbone and hydrophilic side chains.…”
Section: Nanoparticles Based On Self‐assembled π‐Conjugated Small Molmentioning
confidence: 99%